Little house on the prairie - Wilder, Laura Ingalls, 1867-1957.; Williams, Garth (New York : HarperTrophy, 1971)
A family travels from the big woods of Wisconsin to a new home on the prairie, where they build a house, meet neighboring Indians, build a well, and fight a prairie fire.
Keywords: Wilder, Laura Ingalls, -- 1867-1957 -- Juvenile fiction; Wilder, Laura Ingalls, -- 1867-1957 -- Fiction; Frontier and pioneer life -- Great Plains -- Fiction; Family life -- Great Plains -- Fiction; Great Plains -- Fiction